Phototherapy and Mechanism Exploration of Biofilm and Multidrug‐Resistant Helicobacter pylori by Bacteria‐Targeted NIR Photosensitizer. Issue 4 (23rd November 2022) - Qiao, Yanqi; Ma, Yan; Tong, Yue; Liu, Wenting; Wang, Shuo; Zheng, Ying; Men, Changjun; Yu, Jie; Pan, Jie; Wan, Dong; Yin, Yongmei; Zhao, Xiujie; et al.
Abstract: Helicobacter pylori ( H. pylori ) infection has been the leading cause of gastric cancer development. In recent years, the resistance of H. pylori against antibiotic treatment has been a great challenge for most countries worldwide. Since biofilm formation is one of the reasons for the antibiotic resistance of H. pylori, and phototherapy has emerged as a promisingly alternative antibacterial treatment, herein the bacteria‐targeted near‐infrared (NIR) photosensitizer (T780T‐Gu) by combining positively‐charged guanidinium (Gu) with an efficient phototherapeutic agent T780T is developed. The proposed molecule T780T‐Gu exhibits synergistic photothermal therapy/photodynamic therapy effect against both H. pylori biofilms and multidrug‐resistant (MDR) clinical strains. More importantly, the phototherapy mechanism of T780T‐Gu acquired by the RNA‐seq analysis indicates that structural deficiency as well as a decrease in metabolism and defense activity are the possible reasons for the efficient H. pylori phototherapy. Abstract : The infection of multidrug‐resistant (MDR) Helicobacter pylori ( H. pylori ) always threatens public health. To enhance the therapeutic efficacy, especially on MDR H. pylori infection, the bacteria‐targeted photosensitizer T780T‐Gu is here designed and synthesized. Under near‐infrared (NIR) irradiation, the T780T‐Gu showed synergetic photothermal/photodynamic antibacterial potency against clinical MDR H. pylori strains and the biofilms, which provides a promising alternative strategy for H. pylori eradication.